The Japanese Legal System and the Pro Homine Principle in Human Rights Treaties - de Oliveira Mazzuoli, Valerio [UNESP]; Ribeiro, Dilton (Universidad Nacional Autonoma de Mexico, 2015)
The objective and purpose of international human rights is the protection of the human person. Individuals are the primary concern and addressees of human rights norms and principles. Accordingly, all human rights instruments seek the best possible protection for the human person. This theory, which underpins the entire human rights system, is called the pro homine principle. In our view, this pro homine framework of international law was fully accepted by the Japanese Constitution through its Article 11. It forbids restrictive interpretation of rights -limitation of rights must be restrictively interpreted- and it can be a guideline to analyze omissions in human rights norms. Accordingly, Article 11 fits all the criteria of the pro homine principle by crystalizing a true public order which prioritizes the human person setting the parameters to interpret and apply human rights norms. Consequently, this provision allows a dialogue of sources seeking the best norm which could better protect individuals in a specific situation regardless of its international or domestic status or hierarchy.
Keywords: Comparative law; International human rights; Japanese constitutional law; Treaties